Metabolite Profiling of Three Curcuma Species (Zingiberaceae) Based on H-NMR Spectroscopy - Dinar Sari Cahyaningrum Wahyuni; Mutya Puti Wardianti; Yudi Rinanto; Soerya Dewi Marliyana (UNIVERSITAS SEBELAS MARET (UNS), 2019)
Genus Curcuma, Zingiberaceae, is a typical medicinal plant in tropical region especially in Indonesia. It has been studied to have antioxidant, antimicrobial, antitumor, anti-inflammatory and anticancer activities. However, little knowledge of the metabolic profile both primary and secondary metabolites have been reported. Thus, this study aims to investigate metabolic profiling both primary and secondary metabolites simultaneously in the Curcuma species based on proton nuclear magnetic resonance (1H-NMR) spectroscopy. The present work applied metabolomic study which measured the qualitative and quantitative characteristic metabolites. The Curcuma species, Curcuma aeruginosa Roxb., Curcuma xanthorrhiza Roxb., and Curcuma longa L., collected from Nguter, Sukoharjo, Indonesia. Two-dimensional (2D)-NMR techniques were applied to further identify a number of different types of compounds. Multivariate data analysis such as Principal Component Analysis (PCA) applied to reveal differences among species. A clear difference occurred among 3 Curcuma species. Primary metabolites responsible for the discrimination are alanine (C. xanthorrhiza Roxb. was 3.78 times higher than in C. longa L), sugars (C. xanthorrhiza Roxb. were 6.03 and 3.81 times higher in C. aeruginosa Roxb. and C. longa L. respectively). Besides, secondary metabolites which differed among 3 species are curcumin (C. xanthorrhiza Roxb. were 38.25 and 25 times higher than in C. aeruginosa Roxb.) and xanthorrhizol (C. longa L. were 62 and 44.4 times higher than in C aeruginosa Roxb.).